Spring staging in the Svalbard-breeding Pink-footed Goose Anser brachyrhynchus population: site-use changes caused by declining agricultural management? - Tombre, Ingunn M; TÃ¸mmervik, Hans; Gullestad, Nils; Madsen, Jesper (Wildfowl, 2010)
This study used remote sensing data to assess changes in the extent of different habitats at spring staging sites for Pink-footed Geese Anser brachyrhynchus in northern Norway over the years 1975â€“2005. Shifts in goose distribution were analysed in relation to the habitat changes. Abandonment of livestock grazing and mowing of pastures, which has led to re-growth of rough pasture and scrub, is considered to be a major reason for changes in Pink-footed Goose distribution along the flyway in recent decades. The study demonstrates that migrating geese may respond to habitat change by switching to sites where intensive agricultural management has been maintained.